2001
DOI: 10.1038/sj.cr.7290080
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium tumefaciens-mediated transformation of rice with the spider insecticidal gene conferring resistance to leaffolder and striped stem borer

Abstract: Immature embryos of rice varieties Xiushui11 and Chunjiang 11 precultured for 4d were infected and transformed by Agrobacterium tumefaciens strain EHA101/pExT 7 (containing the spider insecticidal gene). The resistant calli were transferred onto the differentiation medium and plants were regenerated. The transformation frequency reached 56% ~ 72% measured as numbers of Geneticin (G418)-resistant calli produced and 36% ~ 60% measured as numbers of transgenic plants regenerated, respectively. PCR and Southern bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The obtained expression vectors were sequenced to verify the gene orientation and transferred into Agrobacterium tumefaciens EHA105 by a freeze–thaw method (Huang et al, 2001). Arabidopsis were transformed by the floral dip method (Clough and Bent, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…The obtained expression vectors were sequenced to verify the gene orientation and transferred into Agrobacterium tumefaciens EHA105 by a freeze–thaw method (Huang et al, 2001). Arabidopsis were transformed by the floral dip method (Clough and Bent, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…As early as 2001, researchers found that introducing the spider insecticidal gene, SpI , into rice enhanced its resistance to the SSB and rice leaf roller [ 107 ]. Li et al [ 129 ] found that the promoter of the rice hydroperoxide lyase gene, OsHPL2 , was specifically induced by the SSB, and then optimized to connect with Cry1C and transformed it into rice.…”
Section: Transgenic Strategiesmentioning
confidence: 99%
“…The rice transformation protocol was based on Liu et al (1998). About 50 dehusked Nipponbare grains were cleaned and washed before being placed on callus N6 agar supplemented with 2,4-Dichlorophenoxyacetic acid (N6D2) (Huang et al, 2001) and grown in the dark at 28 °C for 2 weeks. The grown rice calli were then dissected into smaller sizes (2-3 cm) and placed directly on a fresh N6D2 agar and further incubated in the dark at 28 °C for another 2 weeks.…”
Section: Agrobacterium-mediated Rice Transformationmentioning
confidence: 99%
“…The culture was then grown in Agrobacterium minimal (AB) medium (Liu et al, 1998) with 50 µg/mL Kanamycin antibiotic at 28 °C for 4 h. The culture was then centrifuged for 15 min at 4 °C at 3101 x g. The bacterial pellet was suspended in AAM induction medium (Hiei et al, 1997) with 200 µM acetosyringone and cocultivated with the rice calli for 20 min at room temperature. The calli were then placed on N6D2-AS (Huang et al, 2001) agar layered with sterile Whatman No. 1 filter paper from Sigma-Aldrich (St. Louis, MO).…”
Section: Agrobacterium-mediated Rice Transformationmentioning
confidence: 99%